Hepatocyte circadian clock controls acetaminophen bioactivation through NADPH-cytochrome P450 oxidoreductase - Johnson, Brian P. (Proc Natl Acad Sci U S A, 2014)
The diurnal variation in acetaminophen (APAP) hepatotoxicity (chronotoxicity) reportedly is driven by oscillations in metabolism that are influenced by the circadian phases of feeding and fasting. To determine the relative contributions of the central clock and the hepatocyte circadian clock in modulating the chronotoxicity of APAP, we used a conditional null allele of brain and muscle Arnt-like 1 (Bmal1, aka Mop3 or Arntl) allowing deletion of the clock from hepatocytes while keeping the central and other peripheral clocks (e.g., the clocks controlling food intake) intact. We show that deletion of the hepatocyte clock dramatically reduces APAP bioactivation and toxicity in vivo and in vitro because of a reduction in NADPH-cytochrome P450 oxidoreductase gene expression, protein, and activity.